Analisis Konten TikTok Akun @MetodePenulisanSCI dalam Mendukung Penyelesaian Tugas Akhir - Selly Maharani; Indira Fatra Deni (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the message characteristics of TikTok content on the @MetodePenulisanSCI account and its role in assisting students in completing their final assignments. The focus encompasses message content, meaning, function, presentation format, and the communication context constructed within the content. A qualitative approach with content analysis technique based on Klaus Krippendorff's framework was employed. Data were collected through documentation of six videos selected purposively according to the following criteria: content directly addressing final assignment completion, high interaction levels (likes and comments), and representation of varied educational and motivational message types. The findings reveal that content on the @MetodePenulisanSCI account exhibits consistent message characteristics, namely educational, persuasive, and contextual in nature. Messages are presented in a straightforward, communicative manner and remain relevant to students' experiences, thereby facilitating comprehension and strengthening motivation as well as confidence in completing final assignments. Accordingly, the TikTok content on this account serves not merely as an information medium, but also as a vehicle for supporting informal learning among students